Effects of hydrologic regulation on icefish population dynamics, assemblage structure and fishery yield in Lake Nanyi, China. Issue 4 (14th May 2013) - Wang, Zhongsuo; Yan, Zhongcheng; Xu, Longjun; Lu, Xinxin; Winemiller, Kirk O.; Lei, Guangchun
Abstract: Stock dynamics and demographic parameters of a family of annual icefishes (Salangidae) were investigated in Lake Nanyi in eastern China before and after construction of irrigation infrastructure. After hydroregulation, two of four icefish species, a migratory species ( Hemisalanx brachyrostralis ) and a previously rare species ( Neosalanx tangkahkeii ) were absent from survey samples. The relative abundance of the remained icefish stocks changed greatly. The spring and autumn stocks of N. taihuensis increased from 9.9% and 1.7% to 74.8% and 4.8%, respectively, and N. oligodontis decreased from 84.8% to 20.4%. Total icefish density (CPUE) and yield doubled under the new hydrologic regime. Average adult body size and absolute fecundity of the three persistent icefish stocks decreased, and this could have resulted from slower rates of growth and development of larvae and juveniles in response to greater density of icefishes overall and more intense competition for planktonic food resources during summer and fall.